PROBLEMS AND SOLUTIONS WATER SUPPLY OF THE POPULATION OF THE REPUBLIC OF UZBEKISTAN (World Bulletin of Public Health, 2023)
Development of sanitary norms, rules and hygiene standards aimed at ensuring public health and preventing non-communicable diseases and acute intestinal infections, especially among the population living in rural areas
Keywords: drinking water; small water supply and sanitation systems; prevention; acute intestinal infections